2001
DOI: 10.1017/s1355838201010238
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected, conserved element of the U3 snoRNA is required for Mpp10p association

Abstract: The U3 small nucleolar ribonucleoprotein (snoRNP) is composed of a small nucleolar RNA (snoRNA) and at least 10 proteins. The U3 snoRNA base pairs with the pre-rRNA to carry out the A0, A1, and A2 processing reactions that lead to the release of the 18S rRNA from the nascent pre-rRNA transcript. The yeast U3 snoRNA can be divided into a short 59 domain (nt 1-39) and a larger 39 domain (73 to the 39 end) separated by a stretch of nucleotides called the hinge region (nt 40-72). The sequences required for pre-rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…We did not observe fibrillarin binding to the U3BC RNA in our HeLa nuclear extract; however, under the same conditions we could observe fibrillarin binding to the box C/D motif (30). Furthermore, it has since been shown that the box B/C motif is not required for fibrillarin association with either the yeast or human U3 snoRNAs in vivo (40). 2 We therefore believe that the hU3-55K interacts directly with the 15.5K-bound U3BC RNA complex.…”
Section: Discussionsupporting
confidence: 40%
“…We did not observe fibrillarin binding to the U3BC RNA in our HeLa nuclear extract; however, under the same conditions we could observe fibrillarin binding to the box C/D motif (30). Furthermore, it has since been shown that the box B/C motif is not required for fibrillarin association with either the yeast or human U3 snoRNAs in vivo (40). 2 We therefore believe that the hU3-55K interacts directly with the 15.5K-bound U3BC RNA complex.…”
Section: Discussionsupporting
confidence: 40%
“…In each mutant the complete element was replaced by an unrelated sequence. A similar approach has been used in the analysis of U3 snoRNA in other organisms (30,32,36,37,42,48).…”
Section: Resultsmentioning
confidence: 99%
“…However, mutations mutC, mutB, mutA, mutAЈ, and mut 5Ј hinge were all expressed at lower levels than the wild-type RNA, suggesting that other regions within the human U3 snoRNA may also function in the accumulation of the transcript. Interestingly, mutations in the 5Ј end of the yeast U3 snoRNA also result in reduced expression levels (48), suggesting that this effect is not specific to the human U3 snoRNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both humans and yeast, Imp4p forms a complex with Mpp10p and Imp3p [24,25]. The protein complex then interacts with both U3 snoRNA and 35S rRNA to initiate the maturation of rRNAs [26][27][28]. Imp4p belongs to a protein superfamily that contains a conserved Brix (biogenesis of ribosomes in Xenopus) domain [29].…”
Section: Introductionmentioning
confidence: 99%